The emerging role of MCPH1/BRIT1 in carcinogenesis - Alsolami, Mona; Aboalola, Doaa; Malibari, Dolal; Alghamdi, Tariq; Alshekhi, Walaa; Jad, Hind; Rumbold-Hall, Rea; Altowairqi, Ahlam S.; Bell, Sandra M.; Alsiary, Rawiah Abdullah (Frontiers in Oncology, 2023)
The MCPH1 gene, also known as BRCT-repeat inhibitor of hTERT expression (BRIT1), has three BRCA1 carboxyl-terminal domains which is the important regulator of DNA repair, cell cycle checkpoints and chromosome condensation. MCPH1/BRIT1 is also known as a tumour suppressor in different types of human cancer. The expression level of the MCPH1/BRIT1 gene is decreased in different types of cancers including breast cancer, lung cancer, cervical cancer, prostate cancer, and ovarian cancer, compared with normal tissues. This review showed that deregulation of MCPH1/BRIT1 is significantly associated in many types of tumours especially in breast cancer, lung cancer, ovarian cancer, and colorectal adenocarcinoma, whether at the DNA, RNA, or protein level based on several studies identified from PubMed and google scholar. A common finding of this study is that the loss of MCPH1/BRIT1 gene expression plays a key role in promoting genome instability and mutations supporting its function as a tumour suppressor gene.